2018
DOI: 10.1021/acs.jpcc.7b11462
|View full text |Cite
|
Sign up to set email alerts
|

Dioxygen Activation by Iron Complexes: The Catalytic Role of Intersystem Crossing Dynamics for a Heme-Related Model

Abstract: Enzymes containing heme, nonheme iron, or copper active sites play an essential role in the dioxygen binding and activation for substrate oxidation. The conceptual challenges to the quantitative modeling of this primary catalytic step arise from (1) instrinsic electronic nonadiabaticity of the spin flip events of the triplet dioxygen molecule ( 3 O 2 ), mediated by spin−orbit coupling and (2) possible heat dissipation channels, due to the high exothermicity of dioxygen binding processes. Herein, the spin-forbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 123 publications
1
15
0
Order By: Relevance
“…Many theoretical studies have investigated atomic‐level spin‐inversion mechanisms in O 2 binding with a simplified model heme, namely, a Fe(II)‐porphyrin complex with a proximal imidazole or a related ligand . These theoretical studies have shown that the electronic ground state of the Fe(II)‐porphyrin complex with a d 6 configuration is a quintet spin state and that the second lowest spin state is a triplet state, although the energy difference between these spin states is very small .…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical studies have investigated atomic‐level spin‐inversion mechanisms in O 2 binding with a simplified model heme, namely, a Fe(II)‐porphyrin complex with a proximal imidazole or a related ligand . These theoretical studies have shown that the electronic ground state of the Fe(II)‐porphyrin complex with a d 6 configuration is a quintet spin state and that the second lowest spin state is a triplet state, although the energy difference between these spin states is very small .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the surface area, other factors related to the surface of the iron oxide are important to determine the peroxidaselike activity of the iron oxides. The ability to the binding and the dissociation of the oxygen molecules to the surface of the particles is critical factors with a complexity; for stance, in molecules with an active Fe ion in the core, the dioxygen binding and dissociation dynamics of the resulting iron peroxide species are key points for the catalytic activity of molecule 52 . Besides the surface, the structure and superficial plane are also important in the peroxidase-like of oxides with spinel structure, including the maghemite and the magnetite 53 , among others 3d transition metal oxides with similar structure 54 .…”
Section: Discussionmentioning
confidence: 99%
“…The key steps of the workflow are shown in Figure 2. The samples sufficient molecular conformations were obtained from ab initio dynamic trajectories of previous work (Du et al, 2018), which covered a wide range of conformations related to the spin crossover. Different descriptors were then extracted, FIGURE 1 | The molecular model of this work.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work (Liu et al, 2017;Du et al, 2018), the spin-forbidden dioxygen binding dynamics in a simplified heme model were investigated by the non-adiabatic trajectory surface-hopping dynamics, and this involved the coupled singlet, triplet, and quintuplet states. The results revealed that there existed dominant long-lived, kinetically meta-stable states during the dynamics trajectories, and each meta-stable pattern showed a distinct partial charge population.…”
Section: Introductionmentioning
confidence: 99%